Gas exchange responses during 6‐min walk test in patients with pulmonary arterial hypertension. Issue 1 (16th August 2016) - Morris, Norman R.; Seale, Helen; Harris, Julie; Hall, Kathleen; Lin, Aaron C. W.; Kermeen, Fiona
ABSTRACT: Background and objective: The 6‐min walk test (6MWT) is the most widely utilized method of assessing exercise capacity in pulmonary arterial hypertension (PAH). Cardiopulmonary exercise testing has the advantage of providing additional physiological information over 6MWT. The goals of our study were to describe the addition of gas exchange measurements to 6MWT and to determine how these parameters were related to the severity of PAH in three major subgroups of PAH (idiopathic (IPAH), connective tissue disease‐related (CTPAH) and congenital heart disease‐related (CHPAH)). Methods: Seventy‐six PAH patients (IPAH, n  = 28; CTPAH, n  = 24; CHPAH, n  = 24) completed the 6MWT with simultaneous gas exchange measurements. The 6‐min walk distance (6MWD), oxygen uptake ( V ˙ O2 ), carbon dioxide production ( V ˙ CO2 ), oxygen saturation, minute ventilation to carbon dioxide output ( V ˙ E / V ˙ CO2 ) and end‐tidal partial pressure for carbon dioxide (PET CO2 ) were compared between subgroups, different functional classes (FCs) and pharmacotherapy. Results: Whilst no significant difference in 6MWT was observed, absolute V ˙ O2 and V ˙ CO2 were higher for IPAH ( P  < 0.05). Differences were removed when V ˙ O2 and V ˙ CO2 were expressed relative to body mass (i.e. mL/kg/min). CHPAH had the most significant desaturation during 6MWT (CPAH: 73 ± 15%; CTPAH: 90 ± 8%, IPAH: 92 ± 8%, P  < 0.01). There was no difference in V ˙ E / V ˙ CO2 and PET CO2 between groups; however, New York Health Association (NYHA) FC II performed better than FC III subjects in 6MWT with lower V ˙ E / V ˙ CO2 and higher end‐exercise PET CO2 . Similarly, individuals on more advanced pharmacotherapy (triple therapy vs monotherapy) had poorer gas exchange during exercise. Conclusion: Whilst 6MWT and gas exchange did not differentiate between PAH groups, individuals with more severe disease and on more advanced pharmacotherapy had poorer gas exchange during exercise. Abstract : Pulmonary arterial hypertension (PAH) patients have reduced exercise tolerance and characteristic gas exchange responses. Inclusion of gas exchange measurements during the 6‐min walk test showed that individuals with more severe disease and more advance pharmacotherapy had poorer gas exchange during exercise.